O adolescente autor de ato infracional : rede social e relacionamento interpessoal - Neitzel, Sílvia (2012)
Violence has been the subject of several studies in recent times. It is not rare the association between youth, crime and violence daily on the media seeking to influence the opinion of Brazilian society. However, the literature indicates that adolescents and young people are more frequently victims than perpetrators of violence. The objective of this study is to understand the configuration of social networks and the characteristics of interpersonal relationships within networks of adolescent authors of infraction, which are under socio-educational measures in open environment (supervised freedom) in the municipality of Vila Velha, ES. The sample included ten adolescents aged between 15 and 18 years old. Among the main results, we observe that the teenagers were related to both people involved and not involved in criminal activities. Social networks had a small number of participants, but there were few conflicting and stressful relationships. It was demonstrated that adolescents were not included in other policies beyond the place they comply with the socio-educational measure, or the "yellow house" which was represented by two participants as participating in their networks. No teen was attending school at the time of committing the offense and school was not included as participating in his/her life at present, although declaring interest in resuming his/her studies. Concerning interpersonal relationships, adolescents reported a clear distinction between friends and colleagues. Friends refer usually to subjects not involved in actions related to crime and with whom they report the highest similarity, trust and reciprocity in feelings. On the other hand, colleagues usually are involved in infractions, the relationship is emotionally distant, and no trust and reciprocity are present in the relationship. The adolescents were related to both the nuclear and extended family. In these relationships they perceived reciprocity and trust, although they reported fewer similarities with family than with friends. No professional helping them in the compliance with socio-educational measure is quoted as part of their networks. For participants, having emotionally meaningful relationships with people not involved in criminal activity serves as a protection mechanism against committing illegal acts and contributes to leave behind criminal practices